Improving capacity utilisation of furniture manufacturing SMEs through market based view : a case of Gweru, Zimbabwe . - Mapetere, Denver; Manhiwa, Thelma E R (IJECM Pub UK, 2021)
The growth and reliance on SME in Zimbabwe as well as the launch of the buy Zimbabwe campaign motivated the study in a bid to envisage if SMEs were able to improve their capacity utilisation by adopting market based initiatives. A structured questionnaire was adopted as a data collection instrument and the results are descriptively analysed through distribution frequencies. The study made use of a census sampling technique where 69 owner/managers of SMEs in the furniture manufacturing sector in Gweru Zimbabwe. Furthermore the study made use of furniture manufacturing SMEs clustered at Mkoba 6, Mtapa and DST complex as the key informants. A 100% response rate was achieved allowing the study to draw conclusions and generalize the research results. Results rom the study indicated that SMEs have not been able to adopt effective market based strategies in order to improve their production capacity. SMEs in the furniture manufacturing sector do not carry out any market research activities and thus concentrate more of house hold consumers who bring their own special orders and instructions. The focus on household consumers affects the SME’s working capital positions as they are charging prices below the desired markup policy in order to attract more customers. SMEs should carry out market research on new market and new product development. The study recommends the SMEs to engage in research and development on new strategies used to boost production output and how to implement the strategies effectively.